Der XII. Heroidenbrief--Medea an Jason : Einleitung, Text, und Kommentar : mit einer Beilage--die Fragmente der Tragödie Medea - Ovid, 43 B.C.-17 A.D. or 18 A.D. (Mnemosyne, Supplements, 1997)
This volume contains a critical edition of Ovid's epistle of Medea to Jason, together with the fragments of his lost tragedy Medea , including testimonia . Introduction and commentary deal with matters of language, realia , textual, authenticity, and literary criticism. An examination of the arguments recently put forward against the authenticity of the 12th letter yielded that it cannot be denied Ovidian authorship. Numerous parallels illustrate in particular Ovid's handling of his literary antecedents, notably Euripides and Apollonios. Intensive discussions are also given to questions of genre, epistolary form, influence of elegy and rhetoric, the letter's structure and its position in the collection. The appendix offers a convenient critical summary of the research on Ovid's Medea , together with an extensive commentary on the two fragments.